Combined Antiviral-Antimediator Treatment for the Common Cold - Gwaltney, Jack M. (J Infect Dis, 2002)
A randomized, controlled, double-masked clinical trial was conducted with a combination antiviral-antimediator treatment for experimental rhinovirus colds. In all, 150 healthy men and women (aged 18–51 years) were randomly assigned to 1 of 3 groups: intranasal interferon (IFN)–α2b (6×10(6) U every 12 h × 3) plus oral chlorpheniramine (12 mg extended release) and ibuprofen (400 mg) every 12 h for 4.5 days (n=59 subjects); intranasal placebo plus oral chlorpheniramine and ibuprofen (n=61 subjects); or intranasal and oral placebos (n=30 subjects). Treatment was started 24 h after intranasal viral challenge. During the 4.5 days of treatment with IFN-α2b, chlorpheniramine, and ibuprofen, the daily mean total symptom score was reduced by 33%–73%, compared with placebo. Treatment reduced the severity of rhinorrhea, sneezing, nasal obstruction, sore throat, cough, and headache and reduced nasal mucus production, nasal tissue use, and virus concentrations in nasal secretions. IFN-α2b added to the effectiveness of chlorpheniramine and ibuprofen and was well tolerated